2010
DOI: 10.1084/jem.20091281
|View full text |Cite
|
Sign up to set email alerts
|

Anti-phospholipid human monoclonal antibodies inhibit CCR5-tropic HIV-1 and induce β-chemokines

Abstract: Traditional antibody-mediated neutralization of HIV-1 infection is thought to result from the binding of antibodies to virions, thus preventing virus entry. However, antibodies that broadly neutralize HIV-1 are rare and are not induced by current vaccines. We report that four human anti-phospholipid monoclonal antibodies (mAbs) (PGN632, P1, IS4, and CL1) inhibit HIV-1 CCR5-tropic (R5) primary isolate infection of peripheral blood mononuclear cells (PBMCs) with 80% inhibitory concentrations of <0.02 to ∼10 µg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 60 publications
7
58
0
1
Order By: Relevance
“…It was suggested that SLE and other autoimmune diseases might provide protection against infection,75 but to date no study has isolated the protective factor. One candidate antibody class, antiphospholipid antibodies that can be found in autoimmune disease, was shown to block infection in vitro but testing of patient samples gave inconclusive results 15. Thus, whether SLE or other autoimmune diseases are protective against HIV‐1 infection remains an open question.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that SLE and other autoimmune diseases might provide protection against infection,75 but to date no study has isolated the protective factor. One candidate antibody class, antiphospholipid antibodies that can be found in autoimmune disease, was shown to block infection in vitro but testing of patient samples gave inconclusive results 15. Thus, whether SLE or other autoimmune diseases are protective against HIV‐1 infection remains an open question.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
“…A number of antibody‐mediated functions against HIV‐1 have been studied, including virus capture and phagocytosis,9, 10 antibody‐dependent cell‐mediated virus inhibition,11, 12 antibody‐dependent cell‐mediated cytotoxicity (ADCC),13, 14 chemokine secretion of monocytes stimulated by antibodies,15 and virus neutralization 16, 17, 18. Neutralization has been shown to exert immune pressure on HIV‐1,19, 20 while the role of other antibody‐mediated functions in exerting immune pressure is unclear, primarily because antibodies that mediate ADCC and other activities often also neutralize 21.…”
Section: Introductionmentioning
confidence: 99%
“…Le mécanisme d'inhibition n'a pas encore été clairement identifié même s'il a été proposé que les complexes immuns, fixés aux cellules effectrices par l'intermédiaire des RFcγ, seraient phagocytés puis dégradés dans des lysosomes spécifiques. La fixation des anticorps sur les RFc de cellules effectrices peut aussi déclencher l'activation d'autres mécanismes fonctionnels qui pourraient conduire à une diminution de la réplication virale, comme : -l'induction de cytokines et/ou de chimiokines antivirales [15] ; -la maturation des cellules présentatrices d'antigènes qui favoriserait la restriction virale par des mécanismes postfusion [16]. …”
Section: Mécanisme De Neutralisation Activité Neutralisanteunclassified
“…As a first approach to inhibit enveloped virus multiplication, the functions of lipids incorporated into the viral particle can be targeted by chemical compounds or even by antibodies [161]. This is the case of broad-spectrum antivirals, − some of them already licensed for human use, such as arbidol [162][163][164] −, or inhibitors of membrane fusion [3].…”
Section: Targeting Lipid Metabolism a Novel Antiviral Strategymentioning
confidence: 99%
“…The safety and pharmacokinetics of this antibody have been already evaluated in clinical trials for treatment of other human disorders [201]. Another example of the use of antiphospholipidantibodies to combat a viral disease is provided by HIV, since different antiphospholipid antibodies have shown a broad neutralizing activity against this virus [161].…”
Section: Phosphlipids As Antiviral Targetsmentioning
confidence: 99%